Reimagining Legal Approaches to Technology-Facilitated Violence Against Women in India - Khan, Samina; Nordin, Rohaida; Hassan, Muhamad Sayuti (Hasanuddin Law Review, 2025)
Digital technology has expanded women’s opportunities for expression and participation, while simultaneously enabling new and intensified forms of gender-based violence. In India, technology-facilitated violence against women (TFVW) has increased in scale and complexity, yet existing legal frameworks remain inadequately equipped to address its multidimensional harms. This article identifies a significant gap in Indian law, arguing that the Bharatiya Nyaya Sanhita (BNS) and the Information Technology Act (IT Act) insufficiently recognise psychological harm, informational privacy violations, and non-sexual online abuse, while continuing to rely on patriarchal notions of consent, modesty, and public morality. Adopting a doctrinal legal research methodology informed by feminist jurisprudence, the article examines statutory provisions, judicial interpretations, and enforcement practices governing TFVW in India. It demonstrates how current laws prioritise bodily integrity and obscenity-based regulation, thereby marginalising women’s digital autonomy and reinforcing victim-blaming narratives. Drawing on constitutional principles of equality, dignity, and privacy, the article advances a feminist legal framework that shifts the analytical focus from consent and morality to harm, agency, and structural inequality. The article contributes to feminist legal scholarship by reconceptualising TFVW as a constitutional rights violation and argues for transformative legal reform to address the systemic nature of digital violence against women.